Quality of life and cost of strategies of two chemotherapy lines in metastatic colorectal cancer: results of the FFCD 2000-05 trial. (3rd September 2019) - Lacas, Benjamin; Bouché, Olivier; Etienne, Pierre-Luc; Gasmi, Mohamed; Texereau, Patrick; Gargot, Dany; Lombard-Bohas, Catherine; Azzedine, Ahmed; Denis, Bernard; Geoffroy, Patrick; Auby, Dominique; Michel, Pierre; et al.
ABSTRACT: Objectives : This study compared the cost and quality of life (QoL) of 407 advanced colorectal cancer patients, randomly assigned to receive LV5FU2 followed by FOLFOX6 (sequential strategy) or FOLFOX6 followed by FOLFIRI (combination strategy). Methods : Costs were compared from the French health insurance perspective, until the end of the second line of treatment. Consumed resources, collected during the trial, included medicines, hospitalizations, examinations, and transportation. Valuations were made using 2009 and 2016 tariffs. QoL was assessed using the QLQ-C30 questionnaire and clinically significant variations were searched. Results : In 2009, the mean cost per patient was significantly lower for the sequential strategy compared to the combination strategy (18, 061€ and 23, 119€, p = 0.001). In 2016, the difference was no longer significant (16, 876€ and 18, 090€, p = 0.41) because oxaliplatin and irinotecan became generics. The QoL analysis (292 patients) showed that there was significantly less improvement of global health status in the sequential strategy than in the combination strategy (29% and 42%; p = 0.02) during first-line therapy. No significant differences were observed for emotional functioning (p = 0.45) and physical functioning (p = 0.07) or during second-line therapy. Conclusion : The choice to treat patients with advanced colorectal cancer using one or the other strategy cannot be based on costs or QoL.